Implementation of IC Mux-based data logger in off-grid PLTS - Basrah Pulungan, Ali; Anugrah, Rizki (Department of Electrical Engineering Universitas Negeri Padang, 2025)
Monitoring the performance of Solar Power Plants (PLTS), especially off-grid systems, requires an effective and efficient data logger solution to collect data from multiple measurement points. Commercial data loggers are often constrained by high costs, limited capacity, and lack of flexibility. This research aims to design and implement a low-cost data logger system based on the CD4051B Multiplexer Integrated Circuit (IC) integrated with an Arduino UNO microcontroller. This system is designed to measure key parameters such as current (ACS712) and voltage (voltage sensor) from eight different channels, as well as environmental parameters (DHT11 and BH1750 sensors). The use of the CD4051B MUX IC allows for significant expansion of the Arduino UNO's analog inputs. Time data accuracy is ensured by the DS1307 Real-Time Clock (RTC) module, and data is stored in an SD card for long-term analysis. This approach is expected to produce an economical, reliable, flexible, and scalable data logger solution to meet the monitoring needs of off-grid PLTS, overcome the limitations of commercial data loggers and support performance optimization and maintenance of renewable energy systems